Pengaruh Penambahan Ekstrak Bahan Alami (Bawang Putih dan Temulawak) pada Tubifex sp Terhadap Pertumbuhan Larva Ikan Betok (Anabas testudinius) - Benny Heltonika; Sukendi Sukendi; Ria Hartika (Berkala Perikanan Terubuk, 2015)
The effect of garlic and wild ginger have been to be alternative solution to recovery of fish which attacked by fungus and bacterial disease.  But have not been information how its effects to survivel rate of juvenile, because juvenile usualy attack by fungus disease.  Aimed of this research was how the effect of extract of garlic and wild ginger to climbing fish juvenile.  The method of this research was enrichment of Tubifex sp with garlic and wild ginger extract.  The result of this research was no significant between treatment.